2011
DOI: 10.4103/2229-5119.83963
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of two Indian medicinal plants from Western Ghats, Tamil Nadu

Abstract: Background:The roots of Carissa carandas Linn. (Apocynaceae) and Pergularia daemia (Forsk.) Chiov. (Asclepiadaceae) were used by the tribes of Western Ghats, Tamil Nadu, for the treatment of various liver disorders. Materials and Methods: In the present study, the ethyl acetate fraction of the ethanol extract from roots of C. carandas (CCF) and P. daemia (PDF) were studied against carbon tetrachloride-, paracetamol-, and ethanol-induced hepatotoxicity in rats. Results: Signifi cant hepatoprotective effects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Sitosta-5,23-dien-3β-ol (118) was isolated from the stem bark of Holarrhena antidysenterica (Usmani, 1995). Moreover, β-sitosterol, stigmasterol, sitosterol glucoside (119), and cholest-5-en-3-β-ol (120) were previously isolated from Carissa carandas roots by various researchers (Balakrishnan et al, 2011;Bhaskar & Balakrishnan, 2015;Hegde et al, 2012). The stigmasterol from Carissa carandas was reported for marked anti-inflammatory activity (Galipalli et al, 2015).…”
Section: Sterolsmentioning
confidence: 99%
“…Sitosta-5,23-dien-3β-ol (118) was isolated from the stem bark of Holarrhena antidysenterica (Usmani, 1995). Moreover, β-sitosterol, stigmasterol, sitosterol glucoside (119), and cholest-5-en-3-β-ol (120) were previously isolated from Carissa carandas roots by various researchers (Balakrishnan et al, 2011;Bhaskar & Balakrishnan, 2015;Hegde et al, 2012). The stigmasterol from Carissa carandas was reported for marked anti-inflammatory activity (Galipalli et al, 2015).…”
Section: Sterolsmentioning
confidence: 99%
“…7 ) have indicated possession of hepatoprotective, anti-inflammatory, anti-HIV and anti-hyperlipidemic activities [ 10 ]. They have been isolated from the roots of C. congesta [ 11 , 17 ], C. spinarum [ 37 ], and C. carandas [ 15 , 31 , 38 ]. β -Sitosterol ( 84 ) is the most common sterol in Carissa and it is present in the leaves of C. edulis [ 5 ], roots of C. opaca [ 6 ] and C. carandas [ 15 , 31 , 38 ].…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…So far, only nine Carissa species have been phytochemically studied. Terpenes [ 4 31 ], flavonoids [ 5 , 6 , 19 , 32 , 33 ], lignans [ 5 , 9 , 19 , 26 , 34 36 ], sterols [ 5 , 6 , 11 , 15 , 17 , 31 , 37 , 38 ], simple phenolic compounds [ 5 , 6 , 9 , 13 , 14 , 32 , 36 , 39 ], esters [ 6 , 17 , 21 ], fatty acids [ 17 , 40 ] and other compounds [ 5 – 7 , 9 , 17 , 20 , 21 , 32 , 34 ] were identified across different species. Pharmacological studies on Carissa species have indicated significant antiplasmodial [ 5 , 41 ], diuretic [ 42 ], anticonvulsant [ 43 ], antibacterial [ 9 , 13 , 19 , 44 , 45 ], anti-oxidant and anti-tumor [ 14 , 21 , 24 , 46 – 49 ], antiviral [ 50 – 52 ], antiemetic [ 53 ], anti-hyperlipidemic [ 54 ], analgesic, anti-inflammatory, antipyretic activities [ 55 – 57 ], vasorelaxant [ 58 ], cardioprotective [ 59 ], hepatoprotective [ 38 ,…”
Section: Introductionmentioning
confidence: 99%
“…These activated radicals bind covalently to the macromolecules and induced lipid peroxidative degeneration of biomembranes, leading to liver damage 18 . The rise in serum enzyme levels of AST, ALT and ALP as well as decreased in serum levels of total proteins and albumin has been attributed to the damaged structural integrity of the liver 14 .…”
Section: Fig 4d 4e and 4f: Photomicrographs Of Liver Sections Of Amentioning
confidence: 99%